Islamic da‘wah and civilizational development : a reflection - Mumtaz Ali, Mohammad (International Islamic University Malaysia, 2011)
Generally, DaÑwah is defined as a struggle of the followers of a religion to convert people from other religions. This misrepresentation has not only created misunderstandings about Islam and Islamic movement, it has also affected negatively the image of Islam and Islamic movement in the world. Islam represents the truth concerning human life and ultimate bliss in both this world and the hereafter. The Qur’an is the source of true and authentic knowledge which provides guidance for the well-being of mankind and stands for the development of civilization. This paper contends that the purpose of DaÑwah needs to be presented in the context of civilizational development rather than in the context of religious conversion.